Recurrent emplacement of non-glacial diamictite during the late Paleozoic ice age - Vesely, F. F.; Rodrigues, M. C. N. L.; Rosa, E. L. M. da; Amato, J. A.; Trzaskos, B.; Isbell, J. L.; Fedorchuk, N. D. (Geology, 2018)
23 citations (Crossref) [2023-10-31]
Keywords: dept.esc; peer-reviewed

A new stratigraphic framework built on U-Pb single-zircon TIMS ages and implications for the timing of the penultimate icehouse (Paraná Basin, Brazil) - Griffis, Neil Patrick; Mundil, Roland; Montañez, Isabel Patricia; Isbell, John; Fedorchuk, Nicholas; Vesely, Fernando; Iannuzzi, Roberto; Yin, Qing-Zhu (GSA Bulletin, 2018)
88 citations (Crossref) [2023-10-31]
Keywords: dept.esc; peer-reviewed

The Ferrar Large Igneous Province: Field and geochemical constraints on supra-crustal (high-level) emplacement of the magmatic system - Elliot, David H.; Fleming, Thomas H. (Geological Society, London, Special Publications, 2018)
The Ferrar Large Igneous Province forms a linear outcrop belt for 3250 km across Antarctica, which then diverges into SE Australia and New Zealand. The province comprises numerous sills, a layered mafic intrusion, remnants of extensive lava fields and minor pyroclastic deposits. High-precision zircon geochronology demonstrates a restricted emplacement duration ( < 0.4 myr) at c. 182.7 Ma, and geochemistry demonstrates marked coherence for most of the Ferrar province. Dyke swarms forming magma feeders have not been recognized, but locally have been inferred geophysically. The emplacement order of the various components of the magmatic system at supracrustal levels has been inferred to be from the top-down lavas first, followed by progressively deeper emplacement of sills. This order was primarily controlled by magma density, and the emptying of large differentiated magma bodies from depth. An alternative proposal is that the magma transport paths were through sills, with magmas moving upwards to eventually reach the surface to be erupted as extrusive rocks. These two hypotheses are evaluated in terms of field relationships and geochemistry in the five regional areas where both lavas and sills crop out. Either scenario is possible in one or more instances, but neither hypothesis applies on a province-wide basis. © 2018 The Author(s).
12 citations (Crossref) [2023-10-31]
Keywords: dept.esc; peer-reviewed